2005
DOI: 10.1534/genetics.105.046144
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Extranuclear DNA at Fission Yeast Double-Strand Breaks

Abstract: Proper repair of DNA double-strand breaks (DSBs) is necessary for the maintenance of genomic integrity. Here, a new simple assay was used to study extrachromosomal DSB repair in Schizosaccharomyces pombe. Strikingly, DSB repair was associated with the capture of fission yeast mitochondrial DNA (mtDNA) at high frequency. Capture of mtDNA fragments required the Lig4p/Pku70p nonhomologous end-joining (NHEJ) machinery and its frequency was highly increased in fission yeast cells grown to stationary phase. The fiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 74 publications
5
47
0
Order By: Relevance
“…Typically, 100 ng of linearized or supercoiled DNA were transformed into yeast by using electroporation (31). We chose to use a carrier-free transformation procedure to eliminate possible complications from plasmid recombination reactions with carrier DNA (19,32). Electroporation conditions were 0.75 V, 25 μF, and 200 Ω by using cuvettes with a 0.1-cm gap width (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Typically, 100 ng of linearized or supercoiled DNA were transformed into yeast by using electroporation (31). We chose to use a carrier-free transformation procedure to eliminate possible complications from plasmid recombination reactions with carrier DNA (19,32). Electroporation conditions were 0.75 V, 25 μF, and 200 Ω by using cuvettes with a 0.1-cm gap width (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Two micrograms of phenol/chloroform-purified DNA were used for each yeast transformation. Yeast transformations were performed using a protocol adapted from the lithium acetate method (Okazaki et al 1990) described in Decottignies (2005). The number of Ura 1 colonies was scored after 4 days of incubation at 32°.…”
Section: Methodsmentioning
confidence: 99%
“…Strikingly, this Ku-independent MMEJ pathway was highly reminiscent of a major DSB repair mechanism operating in mammalian cells since short stretches of homologous nucleotides (1-4 bp) are often involved in end-joining events (Roth and Wilson 1986;Thacker et al 1992;King et al 1993;Sasaki et al 2003) although it is not clearly established whether these events are the result of NHEJ or MMEJ. Soon after the experiments were performed in yku70D budding yeast cells, evidence for the conservation of MMEJ throughout evolution was provided by other studies in NHEJ-deficient cells from mammals (Kabotyanski et al 1998;Feldmann et al 2000;Zhong et al 2002;Bentley et al 2004;Guirouilh-Barbat et al 2004;Tsujiet al 2004), Arabidopsis (Heacock et al 2004), S. cerevisiae (Ma et al 2003;Yu and Gabriel 2003), and S. pombe (Manolis et al 2001;Decottignies 2005). Moreover, biochemical purification approaches confirmed that enzymatic requirements for MMEJ are clearly distinct from NHEJ requirements in Xenopus laevis egg extracts (Gottlich et al 1998).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…b Insertions of 100-300 bp that might come from the carrier DNA (Decottignies 2005). c Boldface type indicates bases stemming from the 39 overhangs; underlining indicates possible base pairing involved in the junction.…”
Section: Notementioning
confidence: 99%